Predicting congregate meal program participation: applying the extended theory of planned behavior - Lee, Kuei-I; Gould, Rebecca A. (My University, 2012)
Authorized under Title III-C of Older Americans Act, congregate meal programs provides individuals 60 years of age and older nutritious meals in senior centers. Declining participation in recent years underscores the need to understand factors that affects participation. This study applies the Theory of Planned Behavior (TPB) to explain the intention of community-dwelling older adults to participate in congregate meal programs. One additional variable, past behavior, was added to increase the prediction power of participation intention. A total of 238 participant surveys were collected and analyzed. Seven hypotheses were tested using structural equation modeling. The data fits the TPB model well. All predictor variables (attitude, subjective norm, perceived behavior control and past behavior) had a significant positive effect on participation intention. Perceived behavior control (PBC) had the greatest prediction power on intention. Based on the research findings suggestions were made to increase congregate meal program participation.
Keywords: Theory of planned behavior; Congregate meal program; Participation intention; Past behavior; Salient beliefs